Precise copper ion release and recovery in polycaprolactone nanofiber scaffold: an antibacterial and osteogenic synergistic strategy for guided bone regeneration - Liu, Tongbin; Hassan, Akram; Yousif Alrawas, Matheel Zohair; Cui, Caiyun; Ariffin, Zaihan (Frontiers in Cell and Developmental Biology, 2025)
IntroductionInfection control and bone regeneration remain major challenges in orthopedic therapy. To address these issues, we developed a multifunctional guided bone regeneration (GBR) nanofibrous material based on electrospun polycaprolactone (PCL). This material combines antibacterial and osteogenic properties using polydopamine (PDA) and copper ions (CuCu2+).MethodsPCL nanofibers were produced via electrospinning, and Cu2+ ions were introduced through PDA-mediated surface modification to enable pH-responsive binding and controlled release. The material’s physicochemical properties were evaluated through structural analysis, mechanical testing, and release kinetics. Biological performance was tested using antibacterial assays and osteoblast (MC3T3-E1) cell cultures, including assessments of cell proliferation and key osteogenic gene expression (Runx2, Osx, ALP, OCN).ResultsThe PCL-PDA-Cu composite showed strong structural integrity and mechanical stability. At a Cu2+ concentration of 0.1 M, it demonstrated: 1) strong antibacterial activity; 2) improved osteoblast proliferation; and 3) increased expression of osteogenic genes. The pH-dependent release system maintained effective Cu2+ levels while reducing cytotoxicity.DiscussionBy integrating PDA-mediated Cu2+ coordination with PCL nanofibers, we created a multifunctional platform that balances antimicrobial defense and bone regeneration. This controlled ion delivery strategy shows great promise for bone tissue engineering, especially in infection-prone environments.